preparing bio-fertilizer from sea algae Sargassum vulgare And testing it as a biostimulator and biofertilizer on eggplant plant Sulanum melongena l - ديب جورج; عراج هديل; ديوب وسيم عبد الكريم (Latakia University Journal -Biological Sciences Series, 2021)
This study included preparing the aqueous extract of Sargassum vulgare in several concentrations (10%, 20%, 30%, 40%) and applied as a spray fertilizer on eggplant plants, as one spray every seven days and evaluated as a trait, fertilizer and growth stimulator by studying the characteristics of plants from the length of plants , number of leaves ,number of flowers, and the number of fruits , The results showed that the use of aqueous extract of Sargassum with a concentration of 40% sprayed on the leaves of eggplant plants gave the best results compared to the plants that were fertilized using other concentrations and control plants.